2011
DOI: 10.1021/la201706p
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption Behavior of Hydrophobin and Hydrophobin/Surfactant Mixtures at the Air–Water Interface

Abstract: The adsorption of the surface-active protein hydrophobin, HFBII, and the competitive adsorption of HFBII with the cationic, anionic, and nonionic surfactants hexadecyltrimethylammonium bromide, CTAB, sodium dodecyl sulfate, SDS, and hexaethylene monododecyl ether, C(12)E(6), has been studied using neutron reflectivity, NR. HFBII adsorbs strongly at the air-water interface to form a dense monolayer ∼30 Å thick, with a mean area per molecule of ∼400 Å(2) and a volume fraction of ∼0.7, for concentrations greater … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

22
70
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(94 citation statements)
references
References 35 publications
(68 reference statements)
22
70
2
Order By: Relevance
“…MD simulations of both HFBI and HFBII found that the protein secondary and tertiary structures are largely unchanged at the air-water interface [81,83]. This is consistent with circular dichroism [85] and neutron reflectivity measurements [86], which show limited changes in at the air-water interface. A greater change in the structure of HFBI was found at the water-decane interface [81].…”
Section: Hydrophobin Behaviour At Fluid (Air-water or Oil-water) Intesupporting
confidence: 78%
“…MD simulations of both HFBI and HFBII found that the protein secondary and tertiary structures are largely unchanged at the air-water interface [81,83]. This is consistent with circular dichroism [85] and neutron reflectivity measurements [86], which show limited changes in at the air-water interface. A greater change in the structure of HFBI was found at the water-decane interface [81].…”
Section: Hydrophobin Behaviour At Fluid (Air-water or Oil-water) Intesupporting
confidence: 78%
“…The hydrophobin molecules are "sticky" -they adhere to each other [8,38], as well as to other macromolecules and solid walls [30,39]. These adhesive interactions lead to irreversible aggregation of the HFBII molecules in the bulk of solution.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the comparison of amino acid residue sequence, hydrophobins are classified into two groups, type I and type II [1][2][3][4][5][6][7]. Surface-active properties of hydrophobins have drawn particular interests in self-assembled adsorption behavior of hydrophobins at air/water [8][9][10], water/oil [11][12][13][14], and water/solid interfaces [15][16][17][18][19][20][21][22]. This, in turn, sparked intensive researches to utilize hydrophobins as coating materials for biomedical, technical, and personal care products [23][24][25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%